Food Security, Women, and Higher Education in Aceh - Nurasih Shamadiyah; Nanda Amalia (LPPM Universitas Malikussaleh, 2022)
Universities play a crucial role in promoting sustainable agriculture and community food security. One indicator of a successful education system is the measurement of the quality of the education's output, such as the transfer of information, technology, and agricultural innovations to increase the agricultural productivity of a society and ensure its food security. Even if university students obtained the same information and abilities in lectures, many female students do not work after graduation because they marry and would rather care for their families than implement the knowledge they gained. They have a career in agriculture, but it is not their primary occupation since they support their family. Women as farmers have a substantial and vital impact on household food security. Women have a crucial part in attempts to supply food for the home.